Impact of Home Parenting Environment on Cognitive and Psychomotor Development in Children Under 5 Years Old: A Meta-Analysis - Yang, Qing; Yang, Jinlian; Zheng, Liming; Song, Wei; Yi, Lilan (Frontiers in Pediatrics, 2021)
This study aims to evaluate the relationship between home parenting environment and the cognitive and psychomotor development in children under 5 years old by using meta-analysis. A systematic search of the Chinese and English databases including Pubmed, Embase, the Cochrane Library, CNKI, Weipu, Wanfang, and CBMdisc databases from January 1, 1990, to July 31, 2021, was performed. Articles concerning the relationship between home parenting environment and the cognitive and psychomotor development in children under 5 years old were included. Review Manager 5.4 was used for meta-analysis. Subgroup analysis in terms of age and region were performed. A total of 12 articles were included, including 11 in English and 1 in Chinese. Meta-analysis showed that there was significant relationship between home parenting environment and the cognitive and psychomotor development of children (r = 0.31; r = 0.21). Subgroup analysis showed that correlation between home parenting environment and the cognitive and psychomotor development of children was stronger in children over 18 months compared to those under 17 months [(r = 0.33, r = 0.21) vs. (r = 0.28, r = 0.17)]. The converted summary r value between home parenting environment and cognitive development in developing and developed countries was both 0.32. Conclusively, there is a positive correlation between the home parenting environment and the cognitive and psychomotor development of children under 5 years old. Improving the home parenting environment of children is beneficial to promote their early development.